Self-monitoring and better psychological presence among university students with high and low susceptibility to temptation (Journal of the College of Basic Education, 2023)
1- Self-monitoring of university students with its components.2- The best psychological presence among university students in its dimensions.3- The significance of the difference between the mean scores of students with high and low susceptibility to temptation in self-monitoring with its components.4- The significance of the difference between the average scores of students with high and low susceptibility to attraction in the best psychological existence in its dimensions.5- The correlation between students' scores in self-monitoring and students' scores in susceptibility to temptation.